A Situated Model of Creative Learning. (February 2014) - Tanggaard, Lene
This article puts forward a situated model of creative learning. Most educational studies on creativity tend to concentrate on explaining the relation between teaching and creativity while keeping learning as a secondary concept. However, it has been stated that it is likely that teaching creatively leads to creative learning, suggesting that there is a need to describe the concept of creative learning and to analyse its possible constituents. Accordingly, this presentation introduces an empirically based and theoretically informed model of a creative learning community. The model is based on three key concepts or learning principles which can take different forms in particular settings and social practices. These are respectively: (1) Immersion in the topic of interest, in traditions and in the subject matter, (2) Experimentation and inquiry learning and (3) Resistance from the material of interest. As a theoretical point of departure, this presentation will outline a situated model of creativity and learning, and following this, will introduce a model of creative learning. This presentation will include several empirical examples. In the final part, the model will be discussed in relation to the concept of creative teaching.